An anatomical and experimental study on changes induced by Meloidogyne hapla Chitwood, 1949 in Vitis roots - Joubert, D. J. (Daniel Jakobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhDAgric)--Stellenbosch University, 1971.